Category-specific responses to faces and objects in primate auditory cortex - Hoffman, Kari L.; Ghazanfar, Asif A.; Gauthier, Isabel; Logothetis, Nikos K. (Frontiers in Systems Neuroscience, 2008)
Auditory and visual signals often occur together, and the two sensory channels are known to infl uence each other to facilitate perception. The neural basis of this integration is not well understood, although other forms of multisensory infl uences have been shown to occur at surprisingly early stages of processing in cortex. Primary visual cortex neurons can show frequency-tuning to auditory stimuli, and auditory cortex responds selectively to certain somatosensory stimuli, supporting the possibility that complex visual signals may modulate early stages of auditory processing. To elucidate which auditory regions, if any, are responsive to complex visual stimuli, we recorded from auditory cortex and the superior temporal sulcus while presenting visual stimuli consisting of various objects, neutral faces, and facial expressions generated during vocalization. Both objects and conspecifi c faces elicited robust fi eld potential responses in auditory cortex sites, but the responses varied by category: both neutral and vocalizing faces had a highly consistent negative component (N100) followed by a broader positive component (P180) whereas object responses were more variable in time and shape, but could be discriminated consistently from the responses to faces. The face response did not vary within the face category, i.e., for expressive vs. neutral face stimuli. The presence of responses for both objects and neutral faces suggests that auditory cortex receives highly informative visual input that is not restricted to those stimuli associated with auditory components. These results reveal selectivity for complex visual stimuli in a brain region conventionally described as non-visual "unisensory" cortex.